Sintomas não psicóticos e uso de substâncias psicoativas entre trabalhadores de enfermagem da linha de frente no contexto da covid-19: estudo observacional - Oliveira Junior, Eduardo Gomes de (Universidade Federal de São Carlos, 2023)
To evaluate the presence of non-psychotic symptoms and their relationship with the sociolaboratory profile and use of psychoactive substances by frontline nursing workers. Method: observational, cross-sectional and analytical study composed of a simple random sample of 219 nurses, technicians, and nursing assistants working on the front line in any level of health care. Those who did not fully respond to the research form or were not formally linked to institutions in a city at interior of the State of São Paulo, Brazil were excluded. An online questionnaire was applied with social and labor information, a Self Report Questionnaire (SRQ-20) to identify non-psychotic symptoms and the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) to screen substance use. For data analysis were used descriptive statistics (mean, median, standard deviation, and variance) and inferential statistics (Fisher's Exact Test, Mann Whitney's U Test, and Spearman's Correlation Test). Sample normality was tested using the Shapiro Wilk Test. The odds ratio was calculated to verify whether a given social-occupational variable was related to a greater chance of having non-psychotic symptoms. The significance level adopted for all statistical tests was 5%. Results: It was found that in the majority of the sample, non-psychotic symptoms started before the COVID-19 pandemic and there was maintenance of them associated with differences in gender, history of psychiatric disorder, and workload; however, there was no correlation with substance use. The highest means of psychoactive substance use were found for alcohol and tobacco, respectively. Despite this, the use of such substances was predominantly low risk, i.e., one that does not require intervention. Alcohol abuse was found in 61 (28.2%) of the participants. Regarding tobacco, 26 (11.9%) Conclusion: mental distress was associated with differences in gender, history of psychiatric disorders (anxiety and depression disorders) and workload, however, they were not related to the use of PAS. Nursing on the front line has historically been associated with negative impacts on the mental health of professionals, yet the effects of the COVID-19 pandemic are continuous and may vary according to realities and time frames, opening possibilities for new investigations.
Non-psychotic symptoms and use of psychoactive substances among frontline nursing workers in the context of covid-19: observational study
Keywords: Profissionais de Enfermagem; Sintomas não psicóticos; Uso de substâncias; Pandemia; CIENCIAS DA SAUDE::ENFERMAGEM